The effects of race/ethnicity and physician recommendation for physical activity on physical activity levels and arthritis symptoms among adults with arthritis - Jeremy Huckleby; Faustine Williams; Rose Ramos; Anna María Nápoles (BMC, 2021)
Abstract Background Among U.S. adults with physician-diagnosed arthritis, we examined the association of 1) participant race/ethnicity with meeting physical activity guidelines and arthritis symptoms, and 2) the association of receipt of a physician exercise recommendation with physical activity levels and arthritis symptoms, and whether race/ethnicity moderates these associations. Methods Retrospective, cross-sectional study of National Health Interview Survey pooled data from 2002, 2006, 2009, and 2014 from 27,887 U.S. adults aged ≥18 years with arthritis. Outcomes were meeting aerobic (yes/no) and strengthening guidelines (yes/no), arthritis-associated activity limitations (yes/no) and arthritis-related pain (0-10; higher score = more pain). Predictors were race/ethnicity (White, African American, Latino, and Asian) and receipt of physician recommendation for exercise (yes/no). Covariates included demographic and health characteristics. Results Adjusting for covariates, African Americans were more likely (AOR = 1.27; 95% CI 1.12, 1.43) and Asians were less likely (AOR = 0.75; 95% CI 0.61, 0.92) than Whites to meet muscle strengthening activity guidelines. Compared to Whites, African Americans (B = 0.48; 95% CI 0.24, 0.72) and Latinos (B = 0.44; 95% CI 0.15, 0.72) reported more severe, while Asians reported less severe (B = -0.68; 95% CI -1.22, − 0.14) joint pain. Controlling for covariates, physician exercise recommendation was associated with meeting aerobic (AOR = 1.20; 95% CI 1.11, 1.30) and strengthening (AOR = 1.21; 95% CI 1.11, 1.33) guidelines, regardless of race/ethnicity except for a weak negative association with meeting strengthening guidelines (AOR = 0.85; CI 0.74-0.99) among Latinos. Conclusions Disparities in pain exist for African Americans and Latinos with arthritis. Physician exercise recommendation is critical among patients with arthritis to relieve symptom burden.